2020
DOI: 10.18203/2320-6012.ijrms20200790
|View full text |Cite
|
Sign up to set email alerts
|

Study of coagulation profile and platelet indices in pregnancy induced hypertension with special reference to preeclamptic and eclamptic patients

Abstract: Background: Hypertensive disorders of pregnancy affect about 10% of all pregnant women around the world. A variety of haematological abnormalities may occur in women with Pregnancy Induced Hypertension (PIH), thrombocytopenia being the most common. There is also a definite exaggeration of the hypercoagulable state during PIH. A strong relationship exists between the two most important causes of maternal mortality and morbidity worldwide: Preeclampsia and Post-partum hemorrhage. The aim of this study was to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…9 Haldar et al also found that among the patients with mild PE, severe PE and eclampsia, there was a decrease in the platelet count (/cu mm) (181541.7 versus 170291.7 versus 128291.7 versus 260000, p<0.05) and an increase in the MPV (fl) (10.32 versus 11.21 versus 12.97 versus 8.20, p<0.05), PDW (%) (15.41 versus 18.717 versus 20.6 versus 12.5). 15 Alkholy et al in their study found that among the patients with PE and eclampsia there was a decrease in the platelet count (183.940 versus 139.340 versus 249.120, p<0.001) and an increase in the MPV (9.82 versus 11.07 versus 8.50), and PDW (14.26 versus 17.09 versus 11.01). The results showed that because of increase in platelet destruction as well as platelet turnover among patient having preeclampsia, reducing PC, and increase in MPV and PWD, there is a role in prediction of PE.…”
Section: Distribution Of Bleeding Time (Seconds) Was Comparable Betwe...mentioning
confidence: 91%
See 1 more Smart Citation
“…9 Haldar et al also found that among the patients with mild PE, severe PE and eclampsia, there was a decrease in the platelet count (/cu mm) (181541.7 versus 170291.7 versus 128291.7 versus 260000, p<0.05) and an increase in the MPV (fl) (10.32 versus 11.21 versus 12.97 versus 8.20, p<0.05), PDW (%) (15.41 versus 18.717 versus 20.6 versus 12.5). 15 Alkholy et al in their study found that among the patients with PE and eclampsia there was a decrease in the platelet count (183.940 versus 139.340 versus 249.120, p<0.001) and an increase in the MPV (9.82 versus 11.07 versus 8.50), and PDW (14.26 versus 17.09 versus 11.01). The results showed that because of increase in platelet destruction as well as platelet turnover among patient having preeclampsia, reducing PC, and increase in MPV and PWD, there is a role in prediction of PE.…”
Section: Distribution Of Bleeding Time (Seconds) Was Comparable Betwe...mentioning
confidence: 91%
“…21 Swetha et al found that among the patients with PE and eclampsia there was a decrease in the platelet count (1.14 versus 1.00 versus 2.17) and comparable PT (15.52 versus 15.45 versus 15.41, p>0.05), and an increase in aPTT (37.21 versus 37.29 versus 36.20, p<0.05), CT (min) (6.07 versus 6.72 versus 4.67, p<0.05), BT (min) (4.66 versus 4.79 versus 2.72, p<0.05). 22 15 Patients with IUGR was significantly higher in eclampsia and PE as compared to normal pregnancy. (42.86% (p value<0.0001) and 41.67% (p value<0.0001) versus 0% respectively).…”
Section: Distribution Of Bleeding Time (Seconds) Was Comparable Betwe...mentioning
confidence: 96%